The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physrevlett.107.275001
|View full text |Cite
|
Sign up to set email alerts
|

Ionization by Drift and Ambipolar Electric Fields in Electronegative Capacitive Radio Frequency Plasmas

Abstract: Unlike α- and γ-mode operation, electrons accelerated by strong drift and ambipolar electric fields in the plasma bulk and at the sheath edges are found to dominate the ionization in strongly electronegative discharges. These fields are caused by a low bulk conductivity and local maxima of the electron density at the sheath edges, respectively. This drift-ambipolar mode is investigated by kinetic particle simulations, experimental phase-resolved optical emission spectroscopy, and an analytical model in CF(4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
250
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(283 citation statements)
references
References 34 publications
23
250
1
Order By: Relevance
“…In this Ω-mode [27], a high electric field builds up in the bulk region due to the low electrical conductivity caused by the high electron-neutral collision frequency -this drift field accelerates electrons to high energies to create ionization in the bulk. Similar electron heating and ionization dynamics in the bulk region have been found in dusty plasmas [28][29][30] as well as in discharges operated in various electronegative gases [7,8,[15][16][17][18][19][31][32][33][34][35]. While in case of dust contaminated plasmas the origin of the low electrical conductivity (and that of the high electric field) in the bulk is the loss of charged particles the dust particles, in electronegative plasmas the depleted electron density is due to electron attachment in the discharge center.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this Ω-mode [27], a high electric field builds up in the bulk region due to the low electrical conductivity caused by the high electron-neutral collision frequency -this drift field accelerates electrons to high energies to create ionization in the bulk. Similar electron heating and ionization dynamics in the bulk region have been found in dusty plasmas [28][29][30] as well as in discharges operated in various electronegative gases [7,8,[15][16][17][18][19][31][32][33][34][35]. While in case of dust contaminated plasmas the origin of the low electrical conductivity (and that of the high electric field) in the bulk is the loss of charged particles the dust particles, in electronegative plasmas the depleted electron density is due to electron attachment in the discharge center.…”
Section: Introductionsupporting
confidence: 59%
“…CF 4 discharges exhibit a complex chemistry and become strongly electronegative under typical operating conditions. Under these conditions the plasma composition, the electron heating and ionization dynamics, and the discharge operation differ significantly from those of electropositive discharges [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 96%
“…This can be explained by the different dominant electron power absorption mechanisms in Ar and CF 4 . In Ar, electrons gain energy during the rf cycle predominantly by reflection from the expanding sheaths, whereas in CF 4 , electrons gain energy predominantly by the drift-ambipolar mechanism under many conditions, as described by Schulze et al 25,43 This can be observed in the bottom row of Fig. 4.…”
Section: A Amplitude Asymmetrymentioning
confidence: 55%
“…22 Reducing the gas pressure increases the mean free path for energetic electrons, and this leads to changes to the spatial profiles of excitation and ionization. In addition, Schulze et al 43 demonstrated that the impact of the DA heating decreases at lower pressure, which could also affect the discharge asymmetry. Figure 10 shows the DC self-bias voltage, experimentally measured, and obtained from the PIC simulations, as a function of pressure p, for sawtooth-up and sawtooth-down waveforms, for In all cases, the DC self-bias voltage increases with pressure, similar to argon.…”
Section: Effect Of Gas Pressurementioning
confidence: 99%
“…Their main constituents are typically positive and negative ions, and electrons are only present as a minor species. Such a composition leads to unique effects, e.g., the dominant mechanism of electron energy gain is typically due to the ambipolar and drift electric fields within the ion-ion plasma bulk [12][13][14][15][16][17][18], in sharp contrast with the mechanisms in (more common) electropositive (electron-ion) plasmas where the dynamics of the boundary sheaths conveys energy to the electrons.Being complex dynamical systems, plasmas are susceptible to various instabilities. Strong modulations of the plasma density and light emission -termed as "striations" -have extensively been studied in electropositive DC discharges [19][20][21][22], wherein ion-acoustic or ionization waves form the basics of these features.…”
mentioning
confidence: 99%